Application of Nanotechnology in Analysis and Removal of Heavy Metals in Food and Water Resources - Zhaoyuan Gong; Hiu Ting Chan; Qilei Chen; Hubiao Chen (Nanomaterials, 2021)
Toxic heavy metal contamination in food and water from environmental pollution is a significant public health issue. Heavy metals do not biodegrade easily yet can be enriched hundreds of times by biological magnification, where toxic substances move up the food chain and eventually enter the human body. Nanotechnology as an emerging field has provided significant improvement in heavy metal analysis and removal from complex matrices. Various techniques have been adapted based on nanomaterials for heavy metal analysis, such as electrochemical, colorimetric, fluorescent, and biosensing technology. Multiple categories of nanomaterials have been utilized for heavy metal removal, such as metal oxide nanoparticles, magnetic nanoparticles, graphene and derivatives, and carbon nanotubes. Nanotechnology-based heavy metal analysis and removal from food and water resources has the advantages of wide linear range, low detection and quantification limits, high sensitivity, and good selectivity. There is a need for easy and safe field application of nanomaterial-based approaches.